Florida Statewide Assessment Resource Manual - Florida State Dept. of Education, Tallahassee. Student Assessment Section; Florida State Dept. of Education, Tallahassee. Student Assessment Section ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The Florida Statewide Assessment Program, a result of the Educational Accountability Act of 1971, collects and reports information annually concerning student achievement in the basic skills areas of reading, writing, and mathematics. This publication was prepared for counselors and other school personnel as a resource manual with the following objectives: (1) to present a historical overview of the assessment program and how it relates to the state's accountability program; (2) to briefly explain general principles and procedures in test development, administration, and scoring; and (3) to provide suggestions or activities for counselors and other school personnel in the interpretation and utilization of test data. Legislation related to the program; state board of education administrative rules; skills tested on the State Student Assessment Test, Part II; and Guidelines for Using State Assessment Tests to improve curricular programs are included in the appendices. (Author/PN)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Basic Skills; Criterion Referenced Tests; Educational Assessment; Educational Legislation; Elementary Secondary Education; Mathematics Skills; Minimum Competency Testing; Reading Skills; School Counselors; State Programs; Test Construction; Test Use; Writing Skills; Florida Statewide Assessment Program; Reports, Descriptive; Guides, Non-Classroom.